ANALISIS HUKUM ISLAM TERHADAP PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) UNTUK KESEJAHTERAAN MASYARAKAT SEKITAR PERUSAHAAN PT. GOLD COIN SPECIALITIES KECAMATAN TANJUNG BINTANG LAMPUNG - Munawaroh; Muhammad Iqbal Fasa; A. Khumaidi Ja’far (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The company that implements corporate social responsibility (CSR) is one of them, PT. Gold Coin Specialities in Kec. Tanjung Bintang, South Lampung, where each company has activities to produce goods and services. In carrying out its activities, the company must have a sense of responsibility for the preservation of the environment and society. Besides getting benefits for the company itself, it can also provide welfare for the environment/community, this is related to Corporate Social Responsibility (CSR). The purpose of this study was to determine the analysis of Islamic law on the implementation of CSR for the welfare of the community around the company PT. Natural Fragrance. This study uses the method of field research or field research, the data in this study was carried out using primary data and secondary data. Data collection techniques used by interview, observation, and documentation. Based on the results of research on Corporate Social Responsibility in the perspective of Islamic Law at PT. Gold Coin Specialities Tanjung Bintang, South Lampung, is not in accordance with Islamic law because the company is not responsible for implementing CSR in addition to not being implemented optimally, there is also a lack of transparency or openness between the company and the surrounding community. This company does not carry out the obligations that Islamic law calls obligatory because the company only provides sacks and drums waste, where the waste will be sold and the proceeds from the sale of the waste will be managed by youth organizations for the benefit of the community around the company, blood donors are routinely carried out by employees. , repairing roads around the company, and cleaning up the environment around the company.